2014 IEEE International Conference on Industrial Engineering and Engineering Management 2014
DOI: 10.1109/ieem.2014.7058726
|View full text |Cite
|
Sign up to set email alerts
|

Drivers and barriers in sustainable manufacturing implementation in Malaysian manufacturing firms

Abstract: Sustainable manufacturing practices seek to optimize production efficiency while minimizing environmental impact. Nowadays, the implementation of sustainable manufacturing practices in companies has increased. By implementing sustainable manufacturing practices, firms can gain better access to international markets; enhance business profile, consumer perceptions and corporate reputation and increase the manufacturing capacity. However, the implementation of sustainable manufacturing practices is posed to many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 9 publications
3
42
1
Order By: Relevance
“…Second, EL is found to have a positive influence on ENSPF. This finding agrees well with the results of previous study conducted by [87]. The study described that leaders play a significant role in driving sustainable practices where this leads to organizational efficiency and a reputable green image.…”
Section: Theoretical Contributionsupporting
confidence: 92%
See 2 more Smart Citations
“…Second, EL is found to have a positive influence on ENSPF. This finding agrees well with the results of previous study conducted by [87]. The study described that leaders play a significant role in driving sustainable practices where this leads to organizational efficiency and a reputable green image.…”
Section: Theoretical Contributionsupporting
confidence: 92%
“…The present finding aligned with the past study by [87], who identified that overall cost will increase when sustainable practices are implemented. However, the significant role of the CEOs in sustainable manufacturing implementation remains relevant and vital.…”
Section: Theoretical Contributionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the burning need, implementation of Sustainable Manufacturing (SM) by companies has been unsatisfactory (Kulatunga et al 2013;Alayon et al 2017). This can be attributed to the presence of several endogenous and exogenous barriers such as lack of management support, lack of awareness on how to implement sustainability, lack of government regulations and support besides difficulty in operations and maintenance (Kulatunga et al 2013;Nordin et al 2014). Most of the reported research on SM practices have focussed on a limited set of manufacturing activities that a firm performs.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of sensors are installed (e. g. temperature sensor, speed sensor, defect sensor, water sensor, heat sensor, tire-pressure monitoring sensor, parking sensor, knock sensor, etc.) inside a vehicle to collect the current status of the critical components of a vehicle [33][34][35][36]. The sensors sense the information of a component and the transmitter, which is integrated with the sensor, transmits the information to the CU.…”
Section: Network Componentsmentioning
confidence: 99%